Parental preferences for survey mode of administration, interview versus self-administered, with an asthma management questionnaire. (4th May 2021) - Barry, Frances; Thompson, Lindsey R.; Ravandi, Bahareh; Chang, Todd P.; Halterman, Jill S.; Szilagyi, Peter G.; Okelo, Sande O.
Abstract: Background: National asthma guidelines encourage use of patient surveys to aid clinical assessment. Little is known about how these should be administered in acute care settings such as the emergency department (ED). Objective: Evaluate if parents have a preference for interview versus self-administered surveys in an ED, understand the sociodemographic and clinical characteristics by choice of survey mode of administration, and assess if there is a difference by mode in the parent's perception of an asthma management tool. Methods: A research assistant (RA) surveyed parents of children 2–17 years of age seeking ED asthma care. Parents chose to either self-administer or have an RA-administered survey that included the Pediatric Asthma Control and Communication Instrument-ED version (PACCI-ED). We compared sociodemographic and clinical characteristics and perceptions about the PACCI-ED by mode of survey administration. Results: Of 174 parent participants, 60% chose interviewer-administered surveys. Parents who chose interviewer-administered versus self-administered surveys had lower income, lower educational attainment, and children with uncontrolled asthma ( p < .05). Bivariate and multivariate analyses showed that parents who chose interviewer-administered versus self-administered surveys tended to rate the PACCI-ED more favorably. Conclusions: EDs wishing to systematically use an asthma survey may need to plan appropriate resources for staff to administer them, particularly if they serve populations of lower socioeconomic status.